Sukarno, the Army, and the PKI during the Guided Democracy Era: A Complex Triangular Relationship - Israr, Israr; Anatona, Anatona; Midawati, Midawati (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
This paper analyzes the dynamics of the triangle interaction of President Sukarno, the Indonesian Army, and the Communist Party of Indonesia during the Guided Democracy era, utilizing many new sources. The three predominant political entities that surfaced following the 1959 Presidential Decree not only offered political